G229(P) Using sim to address the needs of the 'forgotten tribe'. (25th October 2020) - Mullen, S; Martin, P; Loughins, L; Wetherup, N
Abstract : Aims: Adolescences make up approximately 19% of the UK population with treatment received split between paediatric and adult services. Research has noted that adolescent attend ED, often as a first preference for illness/injury. The aim was to enhance local knowledge and skills regarding adolescent care with an emphasis placed on emergency presentations. Methods: We developed a one-day teaching programme consisting of mixed teaching modalities (lecture, case-based discussions and simulations). The learning objectives were tailored to the curriculum for paediatric and emergency medicine trainees with input from local experts in adolescent health. A multi-disciplinary faculty facilitated including clinicians from paediatric emergency medicine, emergency medicine, paediatrics, CAMHS (Child and adolescent mental health services) and a speciality organ donation nurse. A total of eight high fidelity simulations were developed and delivered by faculty covering adolescent trauma, DKA, intoxication, the aggressive adolescent, HEEADSSS (psychosocial) assessment, confidentiality, capacity and utilising the Mental Health Act. Amateur actors were employed to play the roles of patients/parents to enhance fidelity. Results: There were 36 participants who attended with 86% (n=31) completing the pre-course questionnaire and 95% (n=34) completing the post course questionnaire. An increase in confidence and knowledge was seen across all domains for all trainees, with an average overall improvement of 30%. The greatest increase in confidence was noted in managing an aggressive adolescent with verbal de-escalation (55.8% vs 82.1% pre and post), managing an adolescent refusing treatment (43.9% vs 80.6% pre and post) and psychosocial evaluation using the HEEADSSS assessment tool (26.2% vs 81.8% pre and post). Feedback was universally positive. Comments included 'Relevant and interactive, learned so much' and 'fantastic course. Covered areas I didn't know I was lacking in.' Delayed feedback at 3 months showed sustained confidence across all areas and evidence of new skills learned being used in clinical practice – in particular use of the HEEADSSS assessment. All candidates would recommend the course to colleagues. Conclusion: This project is an excellent showcase of how we can bring a group of clinicians from various different backgrounds together to drive improvement for a vulnerable group of patients.